HMGB1/PI3K/Akt/mTOR Signaling Participates in the Pathological Process of Acute Lung Injury by Regulating the Maturation and Function of Dendritic Cells - Li, Ruiting; Zou, Xiaojing; Huang, Haiyan; Yu, Yuan; Zhang, Hongmei; Liu, Pei; Pan, Shangwen; Ouyang, Yaqi; Shang, You (Frontiers in Immunology, 2020)
Background: High-mobility group box 1 protein (HMGB1) was identified as a highly conserved DNA binding nuclear protein, which participates in the processes of acute lung injury (ALI). HMGB1 binds to its specific receptors not only to activate the nuclear factor (NF)-κB and mitogen-activated protein kinase (MAPK) pathways but also to regulate activation of the phosphatidylinositol 3′-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway. Mature dendritic cells (DCs) regulate acute lung inflammation and pathological injury in ALI. In addition, studies have shown that activation of the PI3K/AKT/mTOR signaling pathway may regulate the function and maturation of DCs. Objective: Therefore, we speculate that HMGB1-PI3K/Akt/mTOR signaling participates in regulating the pathological process of ALI by regulating the maturation and function of DCs. Methods: Anti-HMGB1 antibody, rHMGB1, or LY294002 (PI3K inhibitor) was administered in a murine model of lipopolysaccharide (LPS)-induced ALI. For in vitro studies, generated bone marrow-derived dendritic cells (BMDCs) primed by LPS were stimulated with the same reagents. The effects of these different treatments were observed on the expression of PI3K, AKT, and mTOR and on the function of DCs. Results: HMGB1 upregulated the expression of PI3K, Akt, and mTOR mRNA and phosphorylated proteins in BMDCs. The HMGB1-PI3K/Akt/mTOR signaling pathway induced the maturation and antigen-presenting ability of lung DCs, mediated the percentage of myeloid DCs (mDCs), and enhanced the adhesion and chemotactic ability of lung DCs. Conclusions: HMGB1-PI3K/Akt/mTOR signaling participates in pathological process of ALI by regulating the maturation and functions of DCs.